Patients with rheumatoid arthritis treated with tumour necrosis factor antagonists increase their participation in the workforce: potential for significant long-term indirect cost gains (data from a population-based registry). Issue 01 (25th May 2009) - Augustsson, J; Neovius, M; Cullinane-Carli, C; Eksborg, S; van Vollenhoven, R F
Abstract : Objective: To investigate the effect of tumour necrosis factor (TNF) antagonist treatment on workforce participation in patients with rheumatoid arthritis (RA). Methods: Data from the Stockholm anti-TNFα follow-up registry (STURE) were used in this observational study. Patients with RA (n = 594) aged 18–55 years, (mean (SD) 40 (9) years) followed for up to 5 years were included with hours worked/week as the main outcome measure. Analyses were performed unadjusted and adjusted for baseline age, disease duration, Health Assessment Questionnaire (HAQ), 28-joint Disease Activity Score (DAS28) and pain score. Results: At baseline patients worked a mean 20 h/week (SD 18). In unadjusted analyses, significant improvements in hours worked/week could already be observed in patients at 6 months (mean, 95% CI) +2.4 h (1.3 to 3.5), with further increases compared to baseline at 1-year (+4.0 h, 2.4 to 5.6) and 2-year follow-up (+6.3 h, 4.2 to 8.4). The trajectory appeared to stabilise at the 3-year (+6.3 h, 3.6 to 8.9), 4-year (+5.3 h, 2.3 to 8.4) and 5-year follow-up (+6.6 h, 3.3 to 10.0). In a mixed piecewise linear regression model, adjusted for age, sex, baseline disease activity, function and pain, an improvement of +4.2 h/week was estimated for the first year followed by an added improvement of +0.5 h/week annually during the years thereafter. Over 5 years of treatment, the expected indirect cost gain corresponded to 40% of the annual anti-TNF drug cost in patients continuing treatment. Conclusion: Data from this population-based registry indicate that biological therapy is associated with increases in workforce participation in a group typically expected to experience progressively deteriorating ability to work. This could result in significant indirect cost benefits to society.